1996
DOI: 10.1007/bf03165049
|View full text |Cite
|
Sign up to set email alerts
|

The value of Tc-99m MIBI SPECT during isosorbide dinitrate infusion in assessment of viable myocardium in patients with myocardial infarction

Abstract: Tc-99m MIBI myocardial SPECT has shown promise for evaluation of coronary artery disease. But its role in predicting myocardial viability is still under investigation. The purpose of this study was to evaluate the value of Tc-99m MIBI myocardial SPECT during isosorbide dinitrate (ISDN) infusion in the assessment of myocardial viability. Thirty-seven patients with previous myocardial infarction (the infarct age ranged from < or = 30 days to 900 days) were studied, of them 13 patients had Tc-99m MIBI studies bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Tc agents have the advantage of superior imaging characteristics of 99mTc and hence this allows more doses to be given, along with reduced tissue attenuation of Tc-agents 47 . Though initial studies have revealed that Tc labelled tracers are less accurate than Tl-201 for detection of viable myocardium, 48 recent studies have shown that using nitroglycerin and 99mTc-myocardial agents, it is possible to achieve comparable sensitivity and specificity for myocardial viability detection as with the use of Tl-201 49, 50…”
Section: Preamble Epidemiology and Evaluationmentioning
confidence: 99%
“…Tc agents have the advantage of superior imaging characteristics of 99mTc and hence this allows more doses to be given, along with reduced tissue attenuation of Tc-agents 47 . Though initial studies have revealed that Tc labelled tracers are less accurate than Tl-201 for detection of viable myocardium, 48 recent studies have shown that using nitroglycerin and 99mTc-myocardial agents, it is possible to achieve comparable sensitivity and specificity for myocardial viability detection as with the use of Tl-201 49, 50…”
Section: Preamble Epidemiology and Evaluationmentioning
confidence: 99%